2019
DOI: 10.2147/cmar.s202628
|View full text |Cite
|
Sign up to set email alerts
|

<p>An integrated prediction model of recurrence in endometrial endometrioid cancers</p>

Abstract: Objectives: Endometrial cancer incidence and mortality are rising in the US. Disease recurrence has been shown to have a significant impact on mortality. However, to date, there are no accurate and validated prediction models that would discriminate which individual patients are likely to recur. Reliably predicting recurrence would be of benefit for treatment decisions following surgery. We present an integrated model constructed with comprehensive clinical, pathological and molecular features desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…As demonstrated in different studies, the availability of several cancer databases and of a huge amount of bioinformatic data on tumor molecular and clinical features has allowed for the accurate identification of useful biomarkers for the early diagnosis of malignant tumors or to predict the risk of cancer relapse [62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in different studies, the availability of several cancer databases and of a huge amount of bioinformatic data on tumor molecular and clinical features has allowed for the accurate identification of useful biomarkers for the early diagnosis of malignant tumors or to predict the risk of cancer relapse [62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial cancer (EC) is one of the three most frequent malignant tumors in the female reproductive system with a gradually increasing morbidity and mortality in recent years, and the onset age is becoming younger. 1 Although, the overall survival (OS) of EC is relatively great, especially the early stage, the 5-year OS rate is above 80%, a large number of patients still develop recurrence, which is one of the major causes resulting in death. 2 The factors of predicting EC recurrence has always been the concentration of clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, our aim was to assess the genetic background of patients with endometrial and ovarian cancer that we diagnose and treat, and compare them with the genetic background of patients with the same cancer types in TCGA. The motivation of this study stemmed from the need to validate a prediction model of clinical outcomes that integrated clinical, pathological, and diverse molecular data: gene and miRNA expression, gene copy number and somatic mutations [ 2 , 3 ]. The validation of these prediction models in TCGA datasets was not ideal, so we wanted to investigate possible reasons for this discordance.…”
Section: Discussionmentioning
confidence: 99%
“…Although TCGA and other publicly available datasets have made these validations much simpler, the limitations of doing so have yet to be fully addressed. For example, in our previous studies designed to predict clinical outcomes by integrating clinical, pathological and molecular features of patients with cancer, we found that the best prediction models, developed using our internal patient cohort (University of Iowa), performed 10–20 percentage points worse in TCGA datasets [ 2 , 3 ]. Based on the characteristics of our population (northern European origin), it was obvious that our patients’ backgrounds seemed to be more homogeneous than the population from which TCGA derived their datasets.…”
Section: Introductionmentioning
confidence: 99%